2013
DOI: 10.17126/joralres.2013.028
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad de la profilaxis analgésica con clonixinato de lisina en exodoncias: ensayo clínico aleatorio.

Abstract: Efectividad de la profilaxis analgésica con clonixinato de lisina en exodoncias: ensayo clínico aleatorio.Aravena P, Benso B, Bertín A & Aravena-Torres R. Efectividad de la profilaxis analgésica con clonixinato de lisina en exodoncias: ensayo clínico aleatorio. J Oral Res 2013; 2(3): 125-130.Resumen: Objetivo: Evaluar la efectividad de la profilaxis analgésica con dosis únicas de clonixinato de lisina (CL 125mg) en pacientes sometidos a extracciones dentales. Metodología: Ensayo clínico aleatorio, doble enmasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…It compares paracetamol and naproxen sodium, the latter presented greater effectiveness for controlling pain after a simple extraction, even in the control group (ibuprofen). The only study on simple extractions was done by Aravena et al 12 , who reported similar results to those found in this study. These researchers conducted a randomized double blind placebo-controlled clinical trial in 54 patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It compares paracetamol and naproxen sodium, the latter presented greater effectiveness for controlling pain after a simple extraction, even in the control group (ibuprofen). The only study on simple extractions was done by Aravena et al 12 , who reported similar results to those found in this study. These researchers conducted a randomized double blind placebo-controlled clinical trial in 54 patients.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the need to make naproxen a painkiller of more rapid onset, has allowed the development of the sodium salt of naproxen 10,11 . On the other hand, extractions generate trauma in the periodontium, which leads to the perception of pain, but such effect can be counteracted by administrating NSAIDs before surgery 12 , under the concept that alleviating pain is more difficult and slow than preventing its emergence 10,13 . This scheme, called analgesic prophylaxis, allows reducing the duration and severity of postoperative pain 10,12 .…”
Section: Introductionmentioning
confidence: 99%